Analysis of Sources of Income and Financial Receipts of the Al-Muttaqien Mosque - Salfa Seti; Fathul Khaeril; Sulistiawati; Fatmawati; Yusriani; Trisna Febrianti; Muttiarni (JEKAMI Journal of Accounting, 2024)
Al-Muttaqien Mosque is a significant place of worship in its community, with various sources of income and financial receipts that support its operations and social activities. This research aims to analyze the mosque's sources of income and the management of its financial revenues. Using a qualitative approach with case studies, this research involved in-depth interviews with mosque administrators, direct observation, and analysis of financial documents. The research results show that the main sources of income for the Al-Muttaqien Mosque include donations, alms, zakat, community donations, as well as economic activities such as renting facilities. Research also reveals the importance of transparency and accountability in managing mosque finances. Even though financial management has been carried out carefully, there are challenges such as limited human resources who have expertise in accounting and the use of technology. Income diversification and waqf management strategies were identified as potential for increasing mosque income in a sustainable manner. This research also emphasizes the need to provide regular financial reports to build congregational trust and increase their participation. With effective management, mosques can have a significant positive impact on society through various social, educational and economic activities. It is hoped that this research will provide useful insights for other mosque administrators in improving the effectiveness and efficiency of financial management in their respective places of worship